IDEATIONAL METAFUNCTION OF THE ‘UN WOMEN’S 2026 INSTAGRAM POSTS: A TRANSITIVITY ANALYSIS OF GENDER INEQUALITY DISCOURSE - Aghniya Zahra Ardya Effendi; Widyastuti (Universitas Negeri Surabaya, 2026)
This research examines how gender inequality is represented in institutional feminist discourse through analyzing the transitivity pattern of UN Women's 2026 Instagram posts. This research employs a descriptive qualitative approach and applies Halliday’s Systemic Functional Linguistics, specifically ideational metafunction, to analyze the process types and participant roles of the selected data. The datasets consist of ten UN Women's 2026 Instagram posts, published between February and March 2026. The findings reveal that only four process types were captured in a total of seventeen clauses. Relational process is the most frequently used, with eight appearances, followed by material processes with six appearances, mental processes with two appearances, and verbal processes with one appearance. In terms of participants' roles, women and girls are most frequently positioned as carriers in relational processes, with four appearances. Furthermore, women and girls were also positioned as affected participants, such as a goal and receiver, with one appearance each. In terms of movement areas, UN Women’s post presents all four movement areas: leadership, economic empowerment, freedom from violence, and peace, security, and humanitarian actions, although economic empowerment is not presented explicitly. These findings suggest that in institutional discourse, gender inequality tends to be portrayed as a structural and socially constructed condition, positioning women both as carriers of social conditions and as actors who actively challenging inequality. For future research, it is recommended to use multimodal discourse analysis to apprehend the non-language aspect of the posts and present more insight into how gender inequality is presented in institutional feminist discourse.